Hypoxia and Integrin-Mediated Epithelial Restitution during Mucosal Inflammation - Goggins, Bridie J.; Chaney, Ciaran; Radford-Smith, Graham L.; Horvat, Jay C.; Keely, Simon (Frontiers in Immunology, 2013)
Epithelial damage and loss of intestinal barrier function are hallmark pathologies of the mucosal inflammation associated with conditions such as inflammatory bowel disease. In order to resolve inflammation and restore intestinal integrity the mucosa must rapidly and effectively repair the epithelial barrier. Epithelial wound healing is a highly complex and co-ordinated process and the factors involved in initiating intestinal epithelial healing are poorly defined. In order for restitution to be successful there must be a balance between epithelial cell migration, proliferation, and differentiation within and adjacent to the inflamed area. Endogenous, compensatory epithelial signaling pathways are activated by the changes in oxygen tensions that accompany inflammation. These signaling pathways induce the activation of key transcription factors, governing anti-apoptotic, and proliferative processes resulting in epithelial cell survival, proliferation, and differentiation at the site of mucosal inflammation. In this review, we will discuss the primary processes involved in epithelial restitution with a focus on the role of hypoxia-inducible factor and epithelial integrins as mediators of epithelial repair following inflammatory injury at the mucosal surface.